Legal Protection Of Broker Company’s Customers Against Commodity Futures Trading In Review Of Law Number 10 Year 2011 (Case Study Of PT. Kontak Perkasa Future) - Rahmat Ari Septiawan (Journal of Law Science, 2021)
This thesis discusses the legal protection of brokerage company customers against commodity futures trading in terms of Law Number 10 of 2011 concerning commodity futures trading, to determine the role of brokerage companies in conducting commodity futures trading transactions and to determine aspects of legal protection provided by brokerage companies. to the agreement that has been made between the brokerage companies in this case is PT..Kontak Perkasa Future and customers/investors; and to know the legality and supervision in the futures trading transactions to customers, business people, to the general public, and especially to futures brokerage companies in Indonesia.This study uses normative juridical research, which is a form of research that describes the applicable laws and regulations associated with legal theories and positive law enforcement practices, which are related to the problems investigated. The data collection techniques that the author uses in this research are interviews, literature study, direct observation or field observation. With the existence of a free market, the freedom of consumers (in this case customers in the Futures trading sector) to choose products and services from a Futures brokerage company is increasingly open. On the other hand, this condition can result in the position of business actors (in this case Futures Brokers) and consumers (customers) becoming unbalanced. The customer is in a weak position and becomes the object of business activity to achieve the maximum profit by business actors (Futures Brokers). The main factor that becomes the weakness of consumers (customers) is that the level of customer awareness of their rights is still very low, plus not all futures brokerage companies that appear have a business license from CoFTRA, therefore a legal protection is needed for brokerage company customers in Indonesia. Commodity futures trading as regulated in Law Number 10 of 2011.